Analisis Proses Reverse Logistics menggunakan Metode Produktivitas Ramah Lingkungan pada CV. Sunflower Amerta - Khalif, Muhammad; Handayani, Wiwik (Jurnal Samudra Ekonomi dan Bisnis, 2023)
This study aims to measure the level of environmental performance in the processing of production defects and to measure the level of eco-friendly productivity in the reverse logistics process. Eco-friendly productivity is a method of simultaneously increasing productivity and environmental performance, while the reverse logistics process is an activity to recover the value of a product. This research focuses on production defects in the three-hole comb product into the product of kalam ngaji. Productivity on CV. Sunflower Amerta experienced a decline in January, which was due to losses in waste production defects. In this process the values ​​of the environmental performance index and the eco-friendly productivity index are still low. Therefore an alternative solution is carried out by implementing a reverse logistics system in order to be able to regain economic value and be able to increase productivity.